Differences in Learning Outcomes Using Direct Learning Models Viewed from Spatial Ability: Study At Basic Survey Working Lesson in the Engineering Surveying - Widiantoro, Oni; Kusnan, Kusnan; Suparji, Suparji; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
The purpose of this research is (1) analyze difference in cognitive students learning outomes are taught using direct learning model compared students learning outomes are taught using direct learning model; (2) analyze difference in cognitive students learning outcomes who have high spatial ability compared low spatial ability; and (3) analyze interaction between learning model and spatial ability towards cognitive students learning outomes. The type of research used is experiment research in faktorial design. Population of this research is all of engineering building students in SMK Negeri 3 Jombang includes Geomatika and Engineering Surveying (TSP). SampleÂ  of this research is X TSP-1 students as experiment group and X TSP-2 students as control group. The results of this research conclude that: (1) students who had taught using direct learning model gotten cognitive learning outcome significantly hingher than students who had taught using direct learning model; (2) students who have high spatial ability will get cognitive learning outcomes significantly higher than low spatial ability; and (3) there is an interaction significantly between learning model and spatial ability toward cognitive students learning.